A map of non-NMDA receptor subunit expression in the vertebrate brain derived from in situ hybridization histochemistry. - Bahn,S; Wisden,W (Humana Pr Inc, 1997)
The Ionotropic Glutamate Receptors provides the first detailed survey of the biochemical, physiological, and pharmacological properties of recombinant ...